ZrOsSi: a Z2 topological metal with a superconducting ground state - Ghosh, Sudeep Kumar; Li, Bin; Xu, Chunqiang; Hillier, Adrian D.; Biswas, Pabitra K.; Xu, Xiaofeng; Shiroka, Toni (Frontiers in Physics, 2023)
The silicide superconductors (Ta, Nb, Zr)OsSi are among the best candidate materials for investigating the interplay of topological order and superconductivity. Here, we investigate in detail the normal-state topological properties of (Ta, Nb, Zr)OsSi, focusing on ZrOsSi, by employing a combination of 29 Si nuclear magnetic resonance (NMR) measurements and firstprinciples band-structure calculations. We show that, while (Ta, Nb)OsSi behave as almost ideal metals, characterized by weak electronic correlations and a relatively low density of states, the replacement of Ta (or Nb) with Zr expands the crystal lattice and shifts ZrOsSi towards an insulator. Our ab initio calculations indicate that ZrOsSi is a Z 2 topological metal with clear surface Dirac cones and properties similar to a doped strong topological insulator.